Juridical review of inheritance disputes arising from absence of gift deed in civil law - Ratu Septia Ningsih; Sulkiah Hendrawati; Wahyudi Wahyudi (Institute Of computer Science (IOCS), 2024)
This research examines inheritance dispute resolution caused by the absence of a deed of gift from a civil law perspective. Oral or informal gifts remain common, particularly among Muslim families, and often trigger disputes after the donor’s death. The study aims to analyze: (1) the legal standing of inheritance disputes without a deed of gift, and (2) the juridical implications for donors, recipients, and other heirs. The research applies a normative-empirical juridical method, combining statutory, conceptual, and case study approaches. Primary data were collected through observation and interviews at Wahyudi and Partner Law Office, while secondary data were obtained from literature studies. The findings reveal that the absence of a deed weakens the recipient’s legal position, leading courts to annul the gift and return the property to the estate. Thus, a deed of gift is essential not only as valid legal evidence but also as preventive legal protection to ensure certainty and avoid disputes.